Synthesis of poly(Acrylonitrile-co-acrylamide) and its chemical modification with hydrazine for removal of Cu(II), Zn(II), Pb(II) and Cr(VI) ions from aqueous solution - Khairuddin, Mastura (2016)
The water pollution caused by heavy metal ions gives serious effect in different form of life especially to human health. The adsorption process is an alternative way for heavy metal ions removal. The polymer-based adsorbent was chosen as material to remove heavy metal ions due to its economic cost, can be prepared with convenient method and excellent capability to make high adsorption towards metal ions. In this study, redox polymerisation of acrylonitrile to form polyacrylonitrile (PAN) and copolymerisation of acrylonitrile with acrylamide to form poly(acrylonitrile(AN)-co acrylamide(AM)) were carried out at 40 °C in deionised water under N2 gas by varying the ratio of acrylonitrile (AN) and acrylamide (AM) in the feed. The highest yield of poly(AN-co-AM) was 75%. Poly(AN-co-AM) was further chemically modified using hydrazine hydrate to form hydrazine-modified poly(AN-co-AM). The poly(AN-co-AM) and hydrazine-modified poly(AN-co-AM) were characterised by Fourier Transform Infrared (FT-IR) spectroscopy, microanalysis, Scanning Electron Microscope (SEM), thermogravimetric analysis (TGA) and amine capacity analysis. The IR spectra showed that the cyano functional group in poly(AN-co-AM) was disappeared which confirmed the chemical modification with hydrazine hydrate. Elemental microanalysis showed that the percentage of nitrogen was increased as the feed ratios of AM were increased. Amine capacities were increased as the mole fraction of AM in poly(AN-co-AM) increased in the feed. Hydrazine-modified poly(AN-co-AM) 97/3 had the highest amine capacity value at 0.8 mmol.g-1. The SEM micrographs revealed that the PAN and poly(AN-co-AM) retained their spherical shape even after chemical modification with hydrazine hydrate. The specific surface area of poly(AN-co-AM) 97/3 was 21 m2.g-1 and increased up to 41 m2.g-1 after chemical modification with hydrazine hydrate. The TG thermogram revealed that the hydrazine-modified poly(AN-co-AM) was thermally more stable than poly(AN-co-AM). The ability of the hydrazine-modified poly(AN-co-AM) to adsorb metal ions; Cu(II), Zn(II), Pb(II) and Cr(VI) ions were carried out by batch experiments and analysed by Inductively Coupled Plasma (ICP). The batch experiments were carried out to study the effects of solution pH, metal ions concentration, contact time, sorbent dosage and sorption temperature on metal ions sorption. The maximum sorptions capacities were achieved at pH 5 with 17.64 mg.g-1, 18.94 mg.g-1, and 20.13 mg.g-1 of sorption for Cu(II), Zn(II) and Pb(II) ions, respectively at 25 °C. However, the optimum sorption capacity of Cr(VI) was occurred at pH 2 with 29.11 mg.g-1 of sorption at 25 C. The sorption capacity of Pb(II) achieved equilibrium (18.8 mg.g-1) at 4-6 hours, followed by Cu(II) (17.3 mg.g-1) at 4-6 hours, Zn(II) (16.6 mg.g-1) at 1-2 hours and Cr(VI) (11.9 mg.g-1) at 2-4 hours. Kinetic studies of Cu(II), Zn(II), Pb(II) and Cr(VI) ions followed the pseudo-second order model, suggesting the chemical sorption as the rate-limiting step of the sorption process. As the heavy metal ions concentration were increased, the sorption capacities were increased from 12.3 mg.g-1 to 63.8 mg.g-1 for Cu(II), 10.2 to 21.8 mg.g-1 for Zn(II), 9.6 mg.g-1 to 35.0 mg.g-1 for Pb(II) and 10.6 mg.g-1 to 13.3 mg.g-1 for Cr(VI). The equilibrium data of Cu(II), Zn(II), Pb(II) and Cr(VI) ions onto hydrazine-modified poly(AN-co-AM) were well described by the Langmuir isotherm. This indicates that the monolayer sorption of the adsorbates possibly occurred on the adsorbent. As the sorbent dosage were increased from 0.05 g to 0.40 g, the sorption capacities were decreased. The sorption process were increased by raising the temperature of Cu(II), Zn(II), and Pb(II) solution system (from 25 up to 75 . Therefore, the sorption processes were endothermic in nature. However, the sorption capacity was decreased as the temperature of Cr(VI) ion solution system was increased. This indicates that the sorption process was exothermic in nature for Cr(VI) ion sorption. The present work demonstrated that the hydrazine-modified poly(AN-co-AM) is a potential adsorbent for applications in heavy metal ions; Cu(II), Zn(II), Pb(II) and Cr(VI) removal from aqueous solution. The adsorption capacities of hydrazinemodified poly(AN-co-AM) under various conditions were comparable with adsorption capacities by other polymeric-based sorbent.